Prarancangan Pabrik Etilen Glikol dari Etilen Oksida dan Air Kapasitas 250.000 ton/tahun - , QUM FIKRI; , Ir. Imam Prasetyo, M.Eng., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Ethylene glycol (mono ethylene glycol) plant from ethylene oxide and water with capacity of 250,000 tons / year is designed to meet the demand of domestic ethylene glycol, ethylene glycol projected domestic needs of 480,460 tons / year in 2015. The plant will operate for 330 days / year. Ethylene glycol product with a purity of 99.9%. The raw materials used are 229,999 ton/year ethylene oxide and 470,433 ton/year water. Based on the operating conditions, the selection of raw materials used and the type of product produced, the plant is classified as high-risk plants. Manufacturing process of ethylene glycol from ethylene oxide and water consists of three main processes, the first is the formation of ethylene glycol from ethylene oxide and water, sulfuric acid catalyst neutralized process, and the last is purification process of ethylene glycol as the main product. Formation process of ethylene glycol from ethylene oxide and water carried by the flow stirred reactor operating conditions 14 atm pressure and at temperature of 100 Â° C using a catalyst H2SO4 (sulfuric acid) 98% as much as 62,707 ton/year. The products produced in the form of ethylene glycol, diethylene glycol, and triethylene glycol. The next stage is the removal of the catalyst H2SO4 with NaOH solution as much as 51.147 ton/year in neutralizer, neutralizer out products such as water and salt Na2SO4 then separated using a filter to be sold as byproduct. The last process is the main product of ethylene glycol purification using multilevel distillation to separate the water first, then the separation of ethylene glycol and diethylene glycol. The yield on distillation such as ethylene glycol 258,307 ton/year and the results in the form of diethylene glycol as 46,524 ton/year as byproduct. The plant will be established in Cilegon, Banten with a land area of 6 hectares and employs 132 employees. To support this process, the utility takes steam as much as 74,980.90 kg / hour, cooling water 1,272,431.54 kg / hour, 5993.81 kVA electrical needs, and compressed air as much as 75.6 m3/hour. Fixed capital required amounted to US$ 60,894,445 + Rp. 194,502,333,484 and working capital US$ 115,341,868 + Rp 21,840,345,345. Profit before tax is Rp. 344,583,634,311. And profit after tax is Rp. 172,291,817,156. From the results of calculations, the Return on Investment (ROI) before taxes 44,93% and 22.46% after tax. Pay Out Time (POT) before taxes 1.82 years, 3.08 years after tax. Break Even Point 40.08%, Shut Down Point 24.61% and Discounted Cash Flow Rate Of Return 25.83%. Ethylene glycol plant design of ethylene oxide in terms of raw material purchase price and selling price losses as prices of raw materials ethylene oxide is more expensive than the price of the product ethylene glycol per one ton of material. So the raw material of ethylene oxide manufactured its own raw materials ethylene and air to plant deserves to be studied. From the results of the feasibility study plants through economic evaluations have been done on plant ethylene glycol from ethylene, air, and water with a production capacity of 250,000 tons / year can be concluded that the plant deserves to be studied further.